Arthroscopic Assistance and Percutaneous Fixation of Complex Intraarticular Metacarpophalangeal Fracture - Jorquera, René; Melibosky, Francisco; Villavicencio, Aldo; Azócar, Camila; Corvalán, Gonzalo; Ramírez, Paula; Paz, Agustín (Journal of Wrist Surgery, 2024)
Comminuted fractures involving the metacarpophalangeal joint are a real challenge for the hand surgeon due to the complexity of their management and the high frequency of functional sequelae caused by the incongruence of the joint surfaces and the injury of soft tissues requiring repair. Metacarpophalangeal joint arthroscopy is an emerging and useful tool for the upper extremity surgeon allowing assisted reduction and percutaneous fixation of these fractures since it permits a complete evaluation of the joint fragments and enables precision in the reduction with the advantage of being a minimally invasive and safe technique. This technique was performed in two patients with complex fractures of the metacarpophalangeal joint with good functional results. In conclusion, this technique is reproducible, with good results and minimal soft-tissue morbidity. It allows a stable osteosynthesis, enabling early joint mobility and rehabilitation, which is essential for function recovery.
Keywords: metacarpophalangeal arthroscopy; comminuted joint fracture; metacarpophalangeal joint; percutaneous reduction and fixation; small joints arthroscopy